A representação do mal no Sutra do Bodhisattva Kṣitigarbha: uma proposta hermenêutica - SAWAYA, Maximiliano Augusto (2021)
The text Ārya-Bodhisattva-Kṣitigarbha Pūrva-praṇidhāna-sūtra, known as the Sutra of the Bodhisattva Kṣitigarbha, among its various themes, deals with the effects of non-virtuous actions (akuśala). These effects appear as intense sufferings, according to some categories of analysis of the afflicting (kleśas) activities (karma), in the aggregates of beings who committed such actions. Some of these distressing activities are known in Portuguese as “ações de maldade” or “ações maldosas”. However, what concept of evil is present in the sutra? This research questions about the representation and presentification of the concept of evil, as well as its narrative representation of the sutra as an interpretive possibility from the perspective based on the Centrist School (Madhyamaka), of the Universalist Tradition (Mahāyāna) in dialogue with the Realist Schools (Sarvāstivāda) and the Virtue System (Geluk), the latter also from the Universalist Tradition (Mahāyāna). The methodological procedure of the research is the hermeneutic one, with an incidence on the Centrist School (Madhyamaka). From an analytical reading of the Sutra of Bodhisattva Kṣitigarbha, the research aims to understand the interpretation of evil based on the Mūlamadhyamakakārikā. The research was developed in three chapters: first, to present how evil is defined and represented in the sutra; second, to understand how the sutra narrative relates to the Madhyamaka theory of interdependence and inherent emptiness of existence (pratītyasamutpāda / śūnyatā); and, third, to relate the definition and representation of evil in the sutra with the Madhyamaka theory, investigating the soteriological value of such hermeneutics. Thus, the research, therefore, aims to map and understand the concept of evil present in the Bodhisattva Kṣitigarbha Sutra through a perspective based on the Centrist School (Madhyamaka), investigating the soteriological possibilities that this perspective allows.